TANGGUNG JAWAB APOTEK DALAM PENJUALAN OBAT-OBATAN DAFTAR G TERHADAP KONSUMEN YANG DIRUGIKAN - Putra, Sabillah Utomo (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
The business agreement between pharmacist and the pharmacy owners can be done as a cooperation. The distinguishes about this cooperation is on the capital which has been spent to establishing the pharmacy. Regarding any disputes which will come out between the pharmacist and the owner must look at the responsibility by each part in running pharmacy. The pharmacies responsibility as a pharmacy manager by give their liability to the consumer. Negligence against the trading of G list medication is a mistakes.